Management of Social Culture Development of Community Village Bobanehena Tourism, North Halmahera District - Nurlaila Nurlaila (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
Tourism Village is a place that has certain characteristics and values that can be a special attraction for tourists with an interest in rural life. This shows that the main attraction of a tourist village is the unique life of the villagers and cannot be found in urban areas, for example showing the unique socio-cultural characteristics of the community. The purpose of this research is to find out that there is a socio-cultural development of the Bobanehena village community in advancing the tourism village. By using descriptive qualitative analysis methods can provide an objective picture of the actual state of the object being investigated. The results obtained are that the community's isorganization and perception of tourists are still weak, so that it affects the support and participation of the community in promoting tourism villages. The community does not yet understand the support that must be given in the progress and development of the Bobanehena tourism village.